Probiotic Weizmannia coagulans MTCC 5856 as adjunct therapy in children's acute diarrhea—a randomized, double-blind, placebo-controlled study - Majeed, Muhammed; Nagabhushanam, Kalyanam; Arumugam, Sivakumar; Chadalavada, Nagarjuna; Seepana, Jyotsna; Annamalai, Thumjaa; Murali, Avinash; Prakasan, Priji; Mundkur, Lakshmi (Frontiers in Pediatrics, 2024)
Objectives: Acute diarrhea in children is generally managed by replacing the lost fluid with oral rehydration solution (ORS). Probiotic supplementation has been reported to reduce the severity of diarrhea. In the present study, we investigated the effect of Weizmannia coagulans (Bacillus coagulans) MTCC 5856, along with ORS on acute diarrhea of all causes in non-hospitalized children. Methods: One hundred and ten children of age between 1 to 10 were enrolled in a doubleblind placebo-controlled study and were randomly allocated to receive W. coagulans MTCC 5856 (4 x 10 8 spores, N=54) + ORS and Zinc (Zn) or a placebo (N=56) + ORS and (Zn) for five days. The consistency of stool, mean duration of diarrhea in hours, mean diarrhea frequency per day and the dehydration status were collected as efficacy endpoints. Safety was evaluated by the occurrence of adverse events. Results: The mean age of children was 5.55±2.57 years (61 boys and 49 girls). The mean duration of diarrhea was 51.31±20.99 hours in W. coagulans MTCC 5856 group and 62.74±24.51 hours in placebo (p = 0.011). The frequency of diarrhea was lower in children supplemented with the probiotic, but the difference was not statistically significant. Perceived efficacy score and dehydration status improved significantly in W. coagulans MTCC 5856 group compared to placebo. No adverse events were recorded. Conclusion: The results of the study suggest that W. coagulans MTCC 5856 could be supplemented along with ORS and Zinc to reduce the duration of diarrhea in non-hospitalized children.Trial Registration: Clinical Trial Registry of India (CTRI) with the registration number CTRI/2022/06/043239 registered in 14/06/2022.